Pregnancy management and outcome in patients with four different tetrahydrobiopterin disorders - Kuseyri Hübschmann, Oya; Opladen, Thomas (Journal of inherited metabolic disease, 2018)
Introduction Inborn errors of tetrahydrobiopterin (BH4) biosynthesis or recycling are a group of very rare neurometabolic diseases. Following growing awareness and improved availability of drug treatment the number of patients with BH4 disorders reaching adulthood is constantly increasing. Pregnancy care of patients with these disorders is therefore a new challenge for clinicians. Methods This retrospective study summarises for the first time clinical and biochemical monitoring data of 16 pregnancies in seven women with different disorders of BH4 metabolism and evaluates treatment regimens before and during pregnancy in relation to the obstetrical outcome and paediatric follow-up. Results Worsening of pre-existing neurological symptoms or occurrence of new symptoms during pregnancy was not observed in most of the cases. Treatment regimens remained mostly unchanged. Pregnancies were not complicated by disease-specific features. Organ abnormalities, miscarriage, prematurity, IUGR and chromosomal changes were occasionally reported, without showing any association with the standard drug treatment for BH4 deficiencies. Conclusion Although our data on 16 pregnancies in seven patients did not present any association of standard drug treatment with an increased rate of pregnancy complications, abnormal obstetrical or paediatric outcome, an intensive clinical and biochemical supervision by a multidisciplinary team before, during and after the pregnancy in any BH4 deficiency is essential since available data on pregnancies in patients with BH4 deficiencies is limited.